Determining the Beaming of Io Decametric Emissions: A Remote Diagnostic to Probe the Io‐Jupiter Interaction. Issue 4 (8th April 2022) - Lamy, L.; Colomban, L.; Zarka, P.; Prangé, R.; Marques, M. S.; Louis, C. K.; Kurth, W. S.; Cecconi, B.; Girard, J. N.; Grießmeier, J.‐M.; Yerin, S.
Abstract: We investigate the beaming of 11 Io‐Jupiter decametric (Io‐DAM) emissions observed by Juno/Waves, the Nançay Decameter Array, and NenuFAR. Using an up‐to‐date magnetic field model and three methods to position the active Io Flux Tube (IFT), we accurately locate the radiosources and determine their emission angle θ from the local magnetic field vector. These methods use (a) updated models of the IFT equatorial lead angle, (b) ultraviolet (UV) images of Jupiter's aurorae, and (c) multi‐point radio measurements. The kinetic energy E e − of source electrons is then inferred from θ in the framework of the Cyclotron Maser Instability. The precise position of the active IFT achieved from methods (b and c) can be used to test the effective plasma density of the Io torus. Simultaneous radio/UV observations reveal that multiple Io‐DAM arcs are associated with multiple UV spots and provide the first direct evidence of an Io‐DAM arc associated with a trans‐hemispheric beam UV spot. Multi‐point radio observations probe the Io‐DAM sources at various altitudes, times and hemispheres. Overall, θ varies a function of frequency (altitude), by decreasing from 75°−80° to 70°−75° over 10−40 MHz with slightly larger values in the northern hemisphere, and independently varies as a function of time (or longitude of Io). Its uncertainty of a few degrees is dominated by the error on the longitude of the active IFT. The inferred values of E e − also vary as a function of altitude and time. For the 11 investigated cases, they range from 3 to 16 keV, with a 6.6 ± 2.7 keV average. Plain Language Summary: The auroral decametric emissions of Jupiter induced by Io (Io‐DAM) are radiated along high latitude magnetic field lines at large aperture angles from the local magnetic field vector, forming a thin hollow cone. In this study, we determine the emission angle θ of 11 cases of Io‐DAM emissions observed by Juno/Waves, the Nançay Decameter Array and the NenuFAR radiotelescope with an up‐to‐date magnetic field model and three different methods aimed at minimizing the uncertainty on θ . These methods accurately position the active Io magnetic Flux Tube (IFT) which hosts the decametric radiosources by using (a) models of the active IFT, (b) ultraviolet images of Jupiter's aurorae, and (c) multi‐point radio measurements. most notably, we found that θ varies within 70°–80° as a function of the source altitude along the field line and independently as a function of time. Assuming that the Io‐DAM emissions are driven by the Cyclotron Maser Instability from energetic electrons, we infer from the measured θ the kinetic energy E e − of the source electrons accelerated by the Io‐Jupiter interaction. The obtained values of E e − also depend on altitude and time and vary between 3 and 16 keV, with a ∼6.5 keV average, in agreement with Juno in situ measurements. Key Points: We derive the Io‐decametric emission angle θ from Juno, Nançay Decameter Array, and NenuFAR data using 3 methods to locate the radio sources θ ( f ) decreases from 75°−80° to 70°−75° over 10–40 MHz and varies both as a function of frequency (or altitude) and time (or longitude of Io) The inferred electron energies amplifying Io‐decametric waves range from 3 to 16 keV also vary as a function of altitude and time